2019
DOI: 10.1177/2158244019861501
|View full text |Cite
|
Sign up to set email alerts
|

Research Motivations and Undergraduate Researchers’ Disciplinary Identity

Abstract: Disciplinary identity, or connection to a particular academic discipline, is constructed through a developmental process across a scholar’s academic life course. Using unique data from an online survey of students at four different colleges and universities, we investigate the extent to which disciplinary identity among undergraduate researchers reflects motivations for participating in research and varies by student discipline. We document key differences in disciplinary identity based upon two internal motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recommendations from the American Association for the Advancement of Science (2011), Boyer Commission on Educating Undergraduates in the Research University (1998), National Academies of Sciences, Engineering, and Medicine (2017), National Research Council (2013), and others (Elgin et al, 2016; Laursen et al, 2010) suggested that quality undergraduate science learning experiences should include student participation in authentic research (Seymour et al, 2004; Spell et al, 2014). Across all disciplines, participation in high-quality research experiences draws from extensive research in the areas of engagement (e.g., Kuh et al, 2008), active learning outcomes (e.g., Chi & Wylie, 2014), and identity (e.g., Davis & Wagner, 2019) and is consistently associated with desirable student outcomes such as interest, engagement, and persistence (Carter et al, 2016; Kuh, 2008; Seymour et al, 2004), particularly for students typically underrepresented in STEM (Eagan et al, 2013; Hernandez et al, 2018).…”
mentioning
confidence: 99%
“…Recommendations from the American Association for the Advancement of Science (2011), Boyer Commission on Educating Undergraduates in the Research University (1998), National Academies of Sciences, Engineering, and Medicine (2017), National Research Council (2013), and others (Elgin et al, 2016; Laursen et al, 2010) suggested that quality undergraduate science learning experiences should include student participation in authentic research (Seymour et al, 2004; Spell et al, 2014). Across all disciplines, participation in high-quality research experiences draws from extensive research in the areas of engagement (e.g., Kuh et al, 2008), active learning outcomes (e.g., Chi & Wylie, 2014), and identity (e.g., Davis & Wagner, 2019) and is consistently associated with desirable student outcomes such as interest, engagement, and persistence (Carter et al, 2016; Kuh, 2008; Seymour et al, 2004), particularly for students typically underrepresented in STEM (Eagan et al, 2013; Hernandez et al, 2018).…”
mentioning
confidence: 99%
“…Students can be knowledge producers [39,40], including being researchers [7,[41][42][43][44][45]. There are many benefits to instilling a research identity into undergraduate students [7,[46][47][48][49][50][51], and shaping a student's research identity can impact their career choices [52][53][54][55]. Disabled students are part of the student cohort.…”
Section: Students As Knowledge Producers Including Researchersmentioning
confidence: 99%
“…The study provided insights into course development and mentoring of research at undergraduate level. Providing more learner support through courses on research methods, sharing research methods adopted by the faculty in their personal research with students (Davis & Wagner, 2019), orientation to research, and research writing offered via online platforms, and widening access to resources such as books, journals, dissertations and free access to databases would enhance the quality of their undergraduate research experience.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Cross-discipline undergraduate students’ perceptions of their research experience revealed that for them, discipline-specific knowledge and skills, and higher order thinking skills are the most important skills required for successful research (Craney et al, 2009). Davis and Wagner (2019) investigated the differences in disciplinary identity among undergraduate researchers and they found that natural science undergraduate researchers were motivated by their intellectual interest as they join existing research projects done by the faculty while the social science undergraduates were driven by their grit or internal perseverance. Davis and Wagner (2019) suggest that natural science faculty should engage students in their projects at the inception, that is, when drafting research questions and they suggest that social science faculty should share their research methods with undergraduates.…”
Section: Introductionmentioning
confidence: 99%